Construction of CdS/Sb2Se3 planar heterojunction by full vapor transport deposition. (December 2022) - Lin, Wen-Wei; Wang, Ning-Wei; Lan, Ze-Ying; Fu, Zhe; Huang, Zhi-Ping; Lin, Li-Mei; Ye, Qing-Ying; Chen, Shui-Yuan; Chen, Gui-Lin
Abstract: In this work, we develop a vapor transport deposition (VTD) technology to prepare CdS film with tetragonal phase for the first time, and then construct a CdS/Sb2 Se3 planar heterojunction by full VTD tactics. Compared with the CdS synthesized by traditional chemical bath deposition (CBD), the CdS-VTD has superior crystalline, conductivity and lower Urbach energy, which also induces the growth orientation of Sb2 Se3 and has a favorable energy level matching structure with Sb2 Se3 . With the improved carrier transport efficiency, finally, the built carbon-based Sb2 Se3 device delivers an efficiency of 4.91%, obviously improved by 15.8% than Sb2 Se3 device with CdS-CBD (4.24%), which is the champion Sb2 Se3 device with full VTD process and pave a successive way for the construction of CdS/Sb2 Se3 planar heterojunction. Highlights: CdS/Sb2 Se3 heterojunction was prepared by full VTD for the first time. CdS-VTD has better crystallinity and conductivity than CdS-CBD. CdS-VTD could induce Sb2 Se3 (hk1) orientation growth. The PCE of Sb2 Se3 solar cells with CdS-VTD was improved by 17%.